The role of staging Computed Tomography on detection of occult metastasis in asymptomatic breast cancer patients. Issue 3 (7th May 2020) - Rajasooriyar, Chrishanthi; Sritharan, Thamayanthy; Chenthuran, Suvithra; Indranath, Kavitha; Surenthirakumaran, Rajendra
Abstract: Background: The use of advanced imaging in staging of breast cancer is on the rise. In countries with limited resources, appropriate patient selection for advanced imaging is mandatory. Aims: We sought to evaluate the number of asymptomatic breast cancer patients with normal staging Chest X‐ray and ultrasound scan of abdomen but were found to have occult metastasis on CT scan of chest, abdomen, and pelvis and to identify predictive factors for occult distant metastasis to guide selection of patients for advanced imaging in resource constrained settings. Methods and Results: This was a descriptive cross‐sectional study carried out in Jaffna, Sri Lanka between March 1, 2012 and March 31, 2019. Statistical analysis was done using SPSS software version 21. The prevalence of occult metastasis was calculated. Bivariate and multivariate analysis was done to identify predictive factors for occult metastasis. There were 233 eligible patients. Only 13% (n = 30) had stage I disease. T1 disease was reported in 21% (n = 50) and axillary nodal metastasis in 48% (n = 135). A total of 15% (n = 34) had occult metastasis on CT scan. Bone (n = 25) was the commonest site of metastasis, followed by lung (n = 10) and liver (n = 06). On bivariate analysis, tumor ( P = .019), nodal ( P = .001), and overall stage ( P = .001) were significant predictors for occult metastasis. On multivariate analysis, nodal metastasis ( P = .045) was the only significant predictor. Conclusion: In unscreened population with limited resources, staging of breast cancer with CT scan should be considered for at least patients with axillary lymph nodal metastasis.